José San Román y Rouyer (1901-1961), life and work - Cuenca González, Concepción (Anales de Hidrología Médica, 2013)
Professor San Roman, second professor in order of succession of the Chair of Medical Hydrology since its establishment in 1912, struggled without rest in order to take Medical Hydrology a leading position among the disciplines of obligatory teaching in Medicine and also to make it reach the same level of development that it had already reached the rest of European countries. We owe him the foundation and management of the Institute "Alfonso Limón Montero" that belongs to the “Consejo Superior de Investigaciones Científicas” (CSIC) and also the creation of its organ of diffusion: the Anales Hispanoamericanos de Hidrología Médica y climatología (1954-1959), both of which disappeared when he was surprised by an early death, when he was still in full professional occupation.